Noncommutative gauge theories and the cosmological constant - Adi Armoni (Physical Review D, 2001)
We discuss the issue of the cosmological constant in non-commutative non-supersymmetric gauge theories. In particular, in orbifold field theories non-commutativity acts as a UV cut-off. We suggest that in these theories quantum corrections give rise to a vacuum energy ρ, that is controlled by the non-commutativity parameter θ, ρ ~ 1/theta^2 (only a soft logarithmic dependence on the Planck scale survives). We demonstrate our claim in a two-loop computation in field theory and by certain higher loop examples. Based on general expressions from string theory, we suggest that the vacuum energy is controlled by non-commutativity to all orders in perturbation